Manajemen Strategik Dalam Pengembangan Rumah Sakit : Sebuah Tinjauan Literatur - Nerissa Arviana; Muhammad Joni Chandra; Yani Restiani Widjaja; Purwadhi Purwadhi (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to provide a systematic analysis of the role of strategic management in hospital development, with a focus on improving operational efficiency, competitiveness, and healthcare service quality. The research employs a qualitative method using a literature review approach, covering articles published between 2014 and 2024. The primary data sources consist of scientific articles from Scopus and Google Scholar databases, using the keywords "strategic management" and "hospital development." The study identifies that adaptive strategic management plays a crucial role in various hospital aspects, including resource optimization, information technology implementation, and patient satisfaction improvement. Additionally, the research highlights the importance of innovation driven by competition among hospitals as a significant factor in healthcare sector development. The findings reveal that hospitals implementing strong business ethics and knowledge management based on information technology are better able to build public trust and achieve long-term sustainability. Moreover, the integration of advanced technologies such as data-driven management systems, digital health applications, and telemedicine has been shown to significantly impact hospitals’ competitiveness in an increasingly competitive market. The study concludes that the application of strategic management grounded in innovation, business ethics, and technology is essential in hospital development, especially in light of new challenges emerging in the healthcare sector, such as service digitalization and growing public demand for high-quality healthcare services. Hence, a holistic and integrated strategic approach will be key to future hospital success.